Voluntary Reporting, Sustainable Reporting and Transition Economy - Masum, Mofijul Hoq; Latiff, Ahmed Razman Abdul; Osman, Mohammad Noor Hisham (International Business and Accounting Research Journal, 2020)
This concept paper aims at exploring the interrelationship among the corporate voluntary reporting, the corporate sustainable reporting and the transition economy from the literatures and frameworks. At this juncture, transition economy refers the economy especially, the transformation of least developing economy to the developing economy as per the criteria of United Nations. Thus, the context of Bangladesh has been used as a ground for the study. The study explores the affiliation among corporate voluntary reporting, corporate sustainable reporting and transition economy from their respective literature and frameworks. From the literature of the corporate voluntary reporting, various dimensions of corporate disclosures have been considered, while the dimensions of sustainability reporting have been considered as per the consolidated set of global reporting index, published by Global Sustainability Standards Boards. In addition, components of transition economy have been considered on the basis of the guideline of the United Nations Economic and Social Council. The similitudes of these three concepts and their consequences are determined on the basis of the literature and frameworks. It is found that the core concepts of corporate voluntary reporting, corporate sustainable reporting and the transition economy are similar, and they are intermingled to each other. We have found that the dimensions of corporate voluntary reporting are the initiation of sustainability reporting that leads a transition economy to gain its status of being a developing economy. The findings of the study imply that the transition economy like Bangladesh has to put more focus on corporate engagement in transforming its economy to the developing economy. As the developing economy is based on trade rather than aid, the government of the country should design their corporate strategies and policies in such a way that leads the country to have a sustainable development. In addition, the findings may also encourage the corporate people to disclose more information regarding sustainability issues. Moreover, the findings may assist the United Nation to consider and reconsider their criteria of graduating any country from one level of economy to another. Finally, the findings can also open the avenue to the academicians to explore the extent of corporate reporting on transition economy.